PENGARUH DANA PIHAK KETIGA TERHADAP PROFITABILITAS PADA BANK SYARIAH INDONESIA PERIODE 2021-2024 - Rosida Kamrul; Itsnaini Chusnul Khotimah (Al-Iqtishad: Jurnal Ekonomi Syariah, 2025)
This study was conducted to determine the effect of third-party funds in the form of savings, deposits and current accounts on profitability at Bank Syariah Indonesia for the period 2021-2024. This study aims to understand the role of third-party funds (TPF) in influencing the level of profitability at Bank Syariah Indonesia. Through this study, it is expected to be analyzed to what extent funds collected from the public - both in the form of savings, current accounts, and deposits - contribute to the bank's ability to generate profits sustainably. This type of research uses quantitative research. The data source in this study is secondary data, namely the financial statements of Bank Syariah Indonesia which are uploaded on the official website of Bank Syariah Indonesia for the period 2021-2024, with the data collection technique being documentation. While the data analysis method is carried out using a simple linear regression model. The results of this study indicate that Third Party Funds have an effect on Profitability based on a simple linear regression analysis test with a t-statistic value of 2.338784 with a Probability value (significant) of 0.0264 (<0.05) so that the DPK variable has an effect on the Profitability variable. The DPK variable has a t-count value greater than the t-table. So that DPK has a partial effect on profitability at Bank Syariah Indonesia.